The moral responsibility of scientists: overview of contemporary epistemological conceptions - Mongiano, Dario Maria (Medicina e Morale, 1989)
The increasing refinement of instruments of investigation has enabled man to probe ever wider and deeper areas of the nature around him, offering him, at the same time, the possibility of intervening in events and directing knowledge toward desired ends. However, these possibilities conceal within them certain risks, precisely at the moment when they become realizable: this is because the element that more than any other differentiates human beings from all other natural beings comes into play: freedom, from which responsibility flows; but what does responsibility mean? In what forms does it present itself? Who can be called responsible and for what? Here are the basic questions to start with.